Jugun Ianfu in Literary Works: A Femicide Reading - Che Man, Siti Hajar; Zaki, Nor Atikah (Malay Literature, 2020)
The field of Literature presents life stories, either explicitly or implicitly. Human life is depicted in literary works unconstrained by time and place. This paper attempts to recollect how women became victims of war crimes during the outbreak of the Second World War, whose impact is felt until now. They were victimized solely because they were women, forced to become sex slaves, raped, tortured and even murdered. The discussion focuses on novels, namely Perawan Remaja dalam Cengkeraman Militer [ Virgin Girls in the Grip of the Military ] (2001) by Pramoedya Ananta Toer and Cantik Itu Luka [Beauty is a Wound] (2004) by Eka Kurniawan. The analysis of the study will use the femicide reading pioneered by Russell. This method will show the "killing of females by males because they are females" through the sexual exploitation of women as jugun ianfu or "comfort women". The fact is, these were women and girls who were forced to become sex slaves. This very tragic war crime has left a deep mark, and literary works that successfully portray itare historical and cultural documents for future generations to ponder and react to. Keywords: Femicide, war crimes, jugun ianfu , sexuality, literature.